MARKETING STRATEGY ANALYSIS OF GOLD PAWN PRODUCTS AT BANK SYARIAH INDONESIA: CASE STUDY AT BANK SYARIAH INDONESIA KCP SIDOARJO AHMAD YANI - Erika; Rukhul Amin; Haqiqi Rafsanjani (RADJA PUBLIKA, 2025)
This study analyzes the marketing strategy of gold pawn products at Bank Syariah Indonesia (BSI) KCP Sidoarjo Ahmad Yani with the Marketing Mix 7P approach. The method used is qualitative with a phenomenological approach, where data is obtained through interviews and observations. The results of the study indicate that the marketing strategy includes products, prices, promotions, places, people, physical evidence, and processes. BSI gold pawn products excel in low deposit fees (ujroh), high estimated value, and fast service through BSI Mobile and Byond. The pricing strategy uses the Basic Gold Price (HDE) based on the average gold price in the last four months and considering competitor prices. Promotion is carried out through flyers, banners, socialization, application pop-ups, and WA Blast. Product distribution is easier with digital services that allow customers to make transactions without going to a branch office. In terms of service, customer service plays a role in providing information and assisting with transactions. Physical evidence can be seen from the office facilities and attractive promotional materials. The gold pawn process is made efficient, from handing over gold to disbursing funds and extending the pawn digitally. Although still facing competition with conventional pawnshops, the 7P-based marketing strategy has proven to increase the appeal of this product. More aggressive innovation and promotion are needed so that BSI gold pawnshops are better known to the public.